Succinate Receptor 1: An Emerging Regulator of Myeloid Cell Function in Inflammation. Issue 1 (January 2021) - Krzak, Grzegorz; Willis, Cory M.; Smith, Jayden A.; Pluchino, Stefano; Peruzzotti-Jametti, Luca
Abstract : The rapidly evolving area of immunometabolism has shed new light on the fundamental properties of products and intermediates of cellular metabolism (metabolites), highlighting their key signaling roles in cell-to-cell communication. Recent evidence identifies the succinate–succinate receptor 1 (SUCNR1) axis as an essential regulator of tissue homeostasis. Succinate signaling via SUCNR1 guides divergent responses in immune cells, which are tissue and context dependent. Herein, we explore the main cellular pathways regulated by the succinate–SUCNR1 axis and focus on the biology of SUCNR1 and its roles influencing the function of myeloid cells. Hence, we identify new therapeutic targets and putative therapeutic approaches aimed at resolving detrimental myeloid cell responses in tissues, including those occurring in the persistently inflamed central nervous system (CNS). Highlights: The signaling properties of the G-protein-coupled SUCNR1 depend on cell and tissue specificity, as well as pathophysiological context. SUCNR1 activation can not only drive proinflammatory responses, but also directly participate in the resolution of inflammation. Succinate signaling via SUCNR1 has a role in the progression of tissue damage and resolution of inflammation in the CNS. Careful consideration of these aspects must be adopted when targeting SUCNR1 signaling to develop new candidate therapies aimed at mitigating the effects of persistent CNS inflammation.